2023
DOI: 10.1007/s00264-023-05710-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cannulated compression headless screws as an alternative implant for superior pubic ramus fracture fixation: a biomechanical study

Abstract: Background/purpose Pubic ramus fractures account for the most common types of pelvic fractures. The standard surgical approach for superior pubic ramus fractures (SPRF) is a minimally invasive percutaneous screw fixation. However, percutaneous closed reduction and internal fixation of anterior pelvic ring injuries have high failure rates of up to 15%. The aim of this biomechanical study was to evaluate the stability of SPRF following stabilization with retrograde placed cannulated compression hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Prompted by the higher failure rates associated with retrograde rami screws, Berk et al 15 performed a biomechanical study evaluating cannulated partially threaded, fully threaded, and headless compression 7.3 mm screws in a pelvic fracture model. They found that fractures treated with partially threaded screws experienced more displacement than fully threaded screws and headless compression screws with cyclical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by the higher failure rates associated with retrograde rami screws, Berk et al 15 performed a biomechanical study evaluating cannulated partially threaded, fully threaded, and headless compression 7.3 mm screws in a pelvic fracture model. They found that fractures treated with partially threaded screws experienced more displacement than fully threaded screws and headless compression screws with cyclical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent follow‐ups showed that all anterior ring injuries healed well. Biomechanical studies 16 , 17 have shown that the stability effects of the reconstruction plate, intramedullary fixation, and external fixation on the anterior ring are similar.…”
Section: Discussionmentioning
confidence: 99%